Physicochemical and Organoleptic Characteristics of Putu Ayu Cakes Made from White Sweet Potato Flour Fortified with Beet Paste - Viana Ugi Makarti; Oktavianti Paramita (Universitas Negeri Padang, 2026)
This study aims to analyze the organoleptic and physicochemical characteristics of putu ayu cakes made with 100% white sweet potato flour substituted for wheat flour, as well as fortified with 30% beet paste as a natural colorant and source of antioxidants. This experimental study with a comparative test design compared the control formulation (P1: 100% white sweet potato flour) with the fortified formulation (P2: 100% white sweet potato flour and 30% beet paste). The parameters tested included hedonic quality assessment, acceptability testing, physical testing, and chemical testing. The hedonic quality assessment involved 3 expert panelists and 80 non-expert panelists for acceptability testing, each using a 1–9 rating scale. The results showed that the addition of beet paste to formulation P2 significantly (p < 0.05) increased aroma (8.67 ± 0.57) and overall acceptability (7.70 ± 0.70) compared to formulation P1 (control). Physically, P2 exhibited a sharp increase in red hue (a*) to 24.31. Chemically, beet pulp fortification increased moisture content to 50.86% and triggered a significant surge in antioxidant activity from 49.97% to 80.98% (p = 0.001). The conclusion of this study indicates that 30% beet pulp fortification optimally enhances the functional value and visual appeal of putu ayu cakes without reducing their sensory acceptability.